Jenis dan kelimpahan ikan tembakul di pantai dumai provinsi riau - Reny Cristina Naibaho; Joko Samiaji; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The study to observe the species composition and abundance on mudskipper fish was conducted in July 2013 in Dumai coastal waters of Riau Province, Indonesia. They study was carried out in providing the lack information on the biological aspects of the mudskipper from Indonesian seas in general, and of the riau’s coasts in particular. They study used a survey method by selecting 3 different stations as the sampling sites. Fish sampels were collected during the low tide. The quadrant were used in the field in facilitating the survey in fish abudance, whilst the identification was commenced in the Laboratory of Marine Biology of University of Riau. The resuld showed that a number of three species of the mudskipper were sucessfully recorded, i.e. Periopthalmodon schlosseri, Periopthalmus variabilis (Eggert) and Baleopthalmus boddarti (Pall). In terms of abudance, the highest, 0,1733 individuals/m2 was recorded in station I and the lowest 0,0867 individuals/m2, was found in stations III. Based on the diversity index (H’), it was reported that the Dumai coast had moderate diversity of the mudskipper. None of the fish was dominating the population since the dominance index (C) was very close to null from each station. It can be concluded that the habitats of mudskipper in Dumai coasts were in the state of unstable due to its E value in which also close to one.   Keywords : Mudskipper, species composition, abudance, Riau